Epistemologia do conhecimento a priori : uma introdução - Magalhães, Carlos Eduardo Dias (2014)
The question of whether there is a priori knowledge or justification has generated much debate and is, indeed, one of the most fundamental questions that presents itself to epistemology. Any answer to it potentially will determine much of our discourse on a wide range of other topics in and about philosophy. There is, between proponents and detractors of the a priori, the understanding that, to consider a belief justified a priori, this justification may not have originated in the experience. However, consensus ends here. Between the parties to the dispute, apriorists and empiricists, there is no consensus as regards the relevant notion of experience , a clear understanding of which is crucial to the a priori/a posteriori distinction. Our purpose in this essay is to discuss the central problems to the dispute, pondering the limits and relevance of their main arguments, with a view to assessing the plausibility of the notion of a priori justification. To this end, following an overview of the conceptual territory of the debate, we focus on the proposals put forward by two of the most influential authors in this topic, Laurence BonJour and Albert Casullo.